False memories in collaborative memory tasks: How do collaborative groups deal with misinformation? - Saraiva, M.; Garrido, M. V.; Albuquerque, P.B. (XV Encontro Nacional da APPE, 2021)
The emergence and transmission of false memories often occur in the course of social interaction. However, the cognitive mechanisms underlying the production of false memories in collaborative memory tasks remain rather unexplored. The present work used the misinformation paradigm to examine how misinformation is transmitted and incorporated in collaborative contexts. In two experiments (N = 304), participants watched a video immediately followed by a recall task (collaborative vs. nominal, Exp.1; individual, Exp.2). Then they completed a questionnaire (collaborative vs. nominal, Exp1; collaborative vs. individual, Exp. 2) containing true and misinformation and a final recall task (collaborative vs. nominal, Exp.1; individual, Exp.2). We expected that collaborative groups would accept less false information due to correction and error pruning mechanisms. Results from Exp.1 revealed that collaborative (vs. nominal) groups produced less false memories. However, they also recalled less correct information, suggesting that collaborative inhibition generalizes to both false and correct information. In Exp.2, participants answering the questionnaire collaboratively (vs. individually) produced less false memories in the final (individual) recall. These results suggest that collaboration has an important role in preventing misinformation transmission.